Pramipexole in patients with Parkinson's disease and marked drug resistant tremor: a randomised, double blind, placebo controlled multicentre study. Issue 6 (1st June 2002) - Pogarell, O; Gasser, T; van Hilten, J J; Spieker, S; Pollentier, S; Meier, D; Oertel, W H
Abstract : Objective: To compare the tremorlytic properties of pramipexole, a non-ergoline dopamine agonist to those of placebo as add on medication in patients with Parkinson's disease. Methods: Eighty four patients with early or advanced Parkinson's disease and marked, drug resistant tremor under a stable and optimised antiparkinsonian medication were included in a double blind, randomised, placebo controlled, multicentre study and assigned to add on treatment (7 week dose titration interval, 4 week maintenance period) with either pramipexole (n=44) or placebo (n=40) as adjunct. The primary end point was the absolute change in tremor score, defined as the sum of tremor related items (16, 20, 21) of the unified Parkinson's disease rating scale (UPDRS) in "on" periods. Secondary end points included the percentage change in tremor score, the absolute and percentage changes in long term EMG tremor registration, and the change in tremor self rating scales. Safety and tolerability were assessed on the basis of adverse events, laboratory tests, ECG, and vital signs. Results: Pramipexole was significantly superior to placebo with a difference between treatment groups in the mean absolute change in tremor score of −4.4 (95% confidence interval (95% CI) −6.2 to −2.5) (p<0.0001), corresponding to a difference in the mean percentage change of −34.7% in favour of pramipexole. The secondary end points were consistent with the significant change in tremor score and provided further evidence for the benefit of pramipexole compared with placebo. Long term EMG registration as an objective measure showed a difference in mean absolute change in tremor occurrence of −15.2% (95%CI −21.4 to −9.0) (p<0.0001), and a difference in the mean percentage change of −45.7% in favour of pramipexole. The treatment effects increased during dose titration and remained stable during the 4 week maintenance dose period until the end of the study. The average daily pramipexole dose during maintenance was 4.1 (SD 0.9) mg. Safety analysis showed an increased rate of fatigue, insomnia, nausea, abdominal pain, and headache under pramipexole, comparable with previous studies. Conclusion: Pramipexole proved to be an effective agent for patients with Parkinson's disease and drug resistant tremor.